Are Seniority-Based Layoffs Discriminatory? The Adverse Impact of Layoffs on Designated Groups - Singh, Gangaram; Reid, Frank (Relations industrielles / Industrial Relations, 1998)
The objectives of this paper are: 1. to determine whether layoffs disproportionately affect members of employment equity designated groups, and 2. to assess the importance of seniority in any adverse impacts. The hypothesis is that seniority is an important criterion for layoffs and that designated group members tend to have less seniority and would therefore be disproportionately affected by layoffs. If this is correct, then layoffs may constitute systemic discrimination since there is a reasonable alternative policy in the form of reduced hours through worksharing, which would affect all groups similarly. Tests confirmed that the probability of a layoff was higher for designated group members. The role of the seniority system in this relationship, however, was contrary to the hypothesis since the relationship between the probability of a layoff and designated group status was weaker at unionized workplaces than at nonuion workplaces. It is concluded that the case for worksharing is strengthened by its potential to reduce the systemic discrimination against designated groups which results from the use of layoffs.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Discrimination; Employment discrimination; Hypotheses; Labor Unions; Layoffs; Personnel policies; Seniority; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies; Work sharing